Chemistry and Technology of Natural and Synthetic Dyes and Pigments - Kumar Samanta, Ashis; Awwad, Nasser S.; Majdooa Algarni, Hamed (IntechOpen, 2020)
This book on 'Chemistry and Technology of Natural and Synthetic Dyes and Pigments' is a priority publication by IntechOpen publisher and it relates to sustainable approaches towards green chemical processing of textiles, specifically on dyeing with natural dyes and pigments as well as dyeing with eco-safe synthetic dyes and chemicals. This book includes the following chapters: an introductory editorial chapter on bio-mordants, bio-dyes and bio-finishes, a review of natural dyes and pigments and its application, pantone-like shade generation with natural colorants, colour-based natural dyes and pigments, printing with natural dyes and pigments, functional property and functional finishes with natural dyes and pigments, eco-safe synthetic dyes and chemicals, and a miscellaneous review on dyed textiles and clothing including natural dye-based herbal textiles.This new book is expected to be useful for dyers of the textile industry as well as to the future researchers in this field.